Dietary patterns in obese pregnant women; influence of a behavioral intervention of diet and physical activity in the UPBEAT randomized controlled trial. Issue 1 (December 2016) - Flynn, Angela; Seed, Paul; Patel, Nashita; Barr, Suzanne; Bell, Ruth; Briley, Annette; Godfrey, Keith; Nelson, Scott; Oteng-Ntim, Eugene; Robinson, Sian; Sanders, Thomas; Sattar, Naveed; et al.
Abstract Background Understanding dietary patterns in obese pregnant women will inform future intervention strategies to improve pregnancy outcomes and the health of the child. The aim of this study was to investigate the effect of a behavioral intervention of diet and physical activity advice on dietary patterns in obese pregnant woman participating in the UPBEAT study, and to explore associations of dietary patterns with pregnancy outcomes. Methods In the UPBEAT randomized controlled trial, pregnant obese women from eight UK multi-ethnic, inner-city populations were randomly assigned to receive a diet/physical activity intervention or standard antenatal care. The dietary intervention aimed to reduce glycemic load and saturated fat intake. Diet was assessed using a food frequency questionnaire (FFQ) at baseline (15+0 -18+6 weeks' gestation), post intervention (27+0 -28+6 weeks) and in late pregnancy (34+0 -36+0 weeks). Dietary patterns were characterized using factor analysis of the baseline FFQ data, and changes compared in the control and intervention arms. Patterns were related to pregnancy outcomes in the combined control/intervention cohort (n  = 1023). Results Four distinct baseline dietary patterns were defined; Fruit and vegetables, African/Caribbean, Processed, and Snacks, which were differently associated with social and demographic factors. The UPBEAT intervention significantly reduced the Processed (−0.14; 95% CI −0.19, −0.08, P <0.0001) and Snacks (−0.24; 95% CI −0.31, −0.17, P <0.0001) pattern scores. In the adjusted model, baseline scores for the African/Caribbean (quartile 4 compared with quartile 1:OR  = 2.46; 95% CI 1.41, 4.30) and Processed (quartile 4 compared with quartile 1:OR  = 2.05; 95% CI 1.23, 3.41) patterns in the entire cohort were associated with increased risk of gestational diabetes. Conclusions In a diverse cohort of obese pregnant women an intensive dietary intervention improved Processed and Snack dietary pattern scores. African/Caribbean and Processed patterns were associated with an increased risk of gestational diabetes, and provide potential targets for future interventions. Trial registration Current controlled trials;ISRCTN89971375